PENGARUH LOCUS OF CONTROL DAN KOMITMEN PROFESIONAL TERHADAP KINERJA AUDITOR INTERNAL - Widarsono, Agus; Oktarina, Mery (Jurnal Riset Akuntansi dan Keuangan, 2015)
This study aims to examine the effect of locus of control and professional commitment on the performance of internal auditors at SMK ISO 9001: 2008 Certified in Bandung. This study consists of locus of control variables, professional commitment and performance of internal auditors. This research was conducted on internal auditors who worked at SMK Bersertifikasi ISO 9001: 2008 in Bandung. The method used in this research is verifikatif survey method. Sample technique used is saturated sample. The hypothesis proposed in this research is (1) locus of control positively affect the performance of internal auditors; (2) professional commitment has a positive effect on the performance of internal auditors; (3) locus of control and professional commitment together positively affect the performance of internal auditors. This hypothesis is tested using spearman rank correlation, whereas coefficient of determination used to know how big influence. From the research result, it can be concluded that: (1) locus of control has positive influence to internal auditor performance with determination value 1,2%. (2) professional commitment has a positive influence on the performance of internal auditors with 2.5% determination value. (3) locus of control and professional commitment have a positive influence on the performance of internal auditors with a value of 6.6% determination.